Optimalisasi Kemampuan Membaca untuk Meningkatkan Kemahiran Menulis Dalam Bahasa Mandarin Mahasiswa Prodi Tiongkok Universitas Al Azhar Indonesia - sri hartati; Tri Budianingsih; Rafita Purna (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
Learning writing skills in Mandarin is often something that is feared and less desirable because of the level of difficulty, because it requires a learning method that can overcome the obstacles faced by learners in this proficiency. This research seeks to provide an alternative method of learning to write by optimizing students' reading abilities. By using a qualitative approach, the author tries to optimize the reading of Chinese texts in learning activities to improve students' writing skills. From the results of this study, it is known that by providing more reading input, students also have more knowledge regarding the topic of writing and its development, better vocabulary mastery and understanding of good writing methods/methods so that it has a positive impact on the development and improvement of writing skills of students in MandarinKeywords – Mandarin, Writing Skills, Reading Abilities, Optimizing.